Mapping of Sapuka Islands water areas, South Sulawesi, Indonesia using Marxan technology for coral reef conservation - JAYA JAYA; ROSWIYANTI ROSWIYANTI; ABDUL RAUF; ANDI NUR APUNG MASSISENG; LUKMAN DARIS; ST ZAENAB (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yaya J, Roswiyanti R, Rauf A, Massiseng ANA, Daris L, Zaenab S. 2024. Mapping of Sapuka Islands water areas, South Sulawesi, Indonesia using Marxan technology for coral reef conservation. Biodiversitas 25: 5012-5023. Mapping coastal and marine conservation areas is essential for supporting sustainable resource management and promoting designated utilization practices. This study aimed to assess the condition of coral reefs and develop a map of conservation zones in the Sapuka Islands' waters, South Sulawesi, Indonesia. The study's novelty lies in providing an updated status of coral reef conditions and identifying optimal zones for conservation within the Sapuka Islands. Data were collected through direct observation, Focus Group Discussions (FGD), social mapping, GPS-based coordinate tracking, underwater photo transects, and the identification of planning units, conservation features, and cost metrics. Findings indicated a decline in coral reef area over the past three years, with coverage reducing from 6,094.67 ha in 2022 to 5,771.67 ha in 2023 and further to 5,559.67 ha in 2024. Several coral genera were identified, including Euphyllia, Acropora, Montipora, Pocillopora, Giniastrea, Sinularia, and Porites. The Marxan analysis identified a core conservation zone encompassing 6,950 ha, distributed across the waters of Sapuka Caddi Island (6,575 ha) and Pelokang Island (375 ha).